Pengaruh Formulasi Tepung Tapioka, Ikan Patin (Pangasius hypophthalmus) Dan Ampas Tahu Terhadap Kadar Air, Protein, Serat Kasar Dan Daya Kembang Serta Daya Terima Kerupuk - Norhasanah Norhasanah; Siti Rahmah; Maymunah Maymunah (HB PRESS, 2020)
Chips made from the mixture of tapioca flour and flavor ingredients such as shrimp or fish. The formulation of chips in this study consist of tapioka flour, patin fish and tofu waste pulp. The purpose of this study was to determine the effect of tapioca formulations, patin fish and tofu waste pulp to water content, protein, crude fiber, and the ability of swell also the acceptable. The method used in this study is an experimental method using RAL with 4 treatments and 3 times replication with the formulation of tapioca flour, pati fish and tofu waste pulp know P0 (100%: 0%: 0%), P1 (43%: 43%: 14 %), P2 (56%: 37%: 7%), P3 (60%: 33%: 7%). Organoleptic test carried out by 25 panelists at the Department of S1 Nutrition STiKes Husada Borneo. Product analysis has done in University of Lambung Mangkurat Laboratory. Data analysis on water content, protein and crude fiber using one way ANOVA, while the acceptable level using Friedman analysis. The results of this study indicate that there is an influence between the formulation of tapioca flour, patin fish and tofu waste pulp to the water content with the highest average value is P3 statistically obtained (P = 0.037 <α = 0.05), the protein with the highest average value is P1 is obtained Statistical results (P = 0,000 <α = 0,05), crude fiber with the highest average value is P3 obtained statistical results (P = 0,000 <α = 0,05) and the ability of swell with the highest average value of P0 obtained statistical results (P = 0,000 <α = 0,05). For the acceptable which includes colour, aroma and taste with the highest value in the P1 category like, the texture with the highest value in the P0 category like. There is a differences in the acceptable of the producing of chips with the formulation of tapioca flour, patin fish and tofu waste pulp produced because p <α = 0.05.